Development of the growth technique on cerium bromide single crystal by Halide‐micro‐pulling‐down method. Issue 6 (June 2017) - Ito, Tomoki; Yokota, Yuui; Kurosawa, Shunsuke; Kamada, Kei; Ohashi, Yuji; Yoshikawa, Akira
Abstract : We developed the growth technique of the CeBr3 scintillator single crystal by a Halide‐micro‐pulling‐down (H‐μ‐PD) method. Four‐types after‐heaters with different configurations were prepared to control the temperature gradient around the liquid‐solid interface during crystal growth. CeBr3 single crystal with high transparency could be obtained by the high temperature gradient. The light yield and the decay time under γ‐ray irradiation were ∼68, 000 ph/MeV and 19 ns, respectively. Abstract : We developed the growth technique of the CeBr3 scintillator single crystal by a Halide‐micro‐pulling‐down (H‐μ‐PD) method using a carbon crucible with a die under suitable temperature gradient. Four‐types after‐heaters with different configurations were prepared to control the temperature gradient around the liquid‐solid interface during crystal growth. The high temperature gradient resulted in the stable meniscus during the crystal growth and the CeBr3 single crystal with high transparency could be obtained. The light yield and the decay time under γ‐ray irradiation were ∼68, 000 ph/MeV and 19 ns, respectively.